An Analysis of Perceived Organizational Support and Organizational Climate on the Supportive Leadership–Employee Wellbeing Linkage in the Lebanese Academic Sector - Fida Ragheb Hassanein; Amira Daouk; Najib Bou Zakhem; Ranim Ahmad ElSayed; Suha Tahan; Hassan Houmani; Hala Koleilat Al Dilby (Administrative Sciences)
Leaders are determinants of employee behavioral and work outcomes across industries. Notably, in the higher education sector where staff are required to perform various tasks while delivering knowledge to the younger generation, thus shaping the future of society. The current research employs social exchange and social identity theories to investigate the direct effect of supportive leadership on the wellbeing of employees. The indirect effects of organizational climate as a mediator, and perceived organizational support as a moderator are examined to better understand the underlying predictors of wellbeing in academia. Surveys were collected using a purposive and convenience sampling method and analyzed using partial least squares–structural equation modeling (PLS-SEM) with Smart-PLS software, Version 3. The results show that the wellbeing of academic staff is not only influenced by the role and behavior of leaders but also the dynamics that surround it, namely, organizational climate aligned with the leadership efforts, and perceived organizational support among the staff that provides security, sense of belonging, and identity, leading to improved wellbeing. Organizational support when perceived by staff members can significantly boost the effectiveness of leadership efforts towards enhancing employees’ wellbeing.